Gender relations in forest societies in Asia - Kelkar, G.; Nathan, D. (2001)
Based on fieldwork several indigenous societies in South and Southeast Asia, this article explores the change in gender relations from a matrilineal and/or egalitarian system to one where male domination is present as the norm. We looked at changes in gender relations in forest societies in four situations: (a) colonial and state rule over forest communities and the takeover of forests; (b) historical and contemporary revolts of forest-dwelling women and men re-establish community control over forests; (c) the response of national states to these autonomy movements by shifting to devolution as a policy; and (d) the current situation, where women's inclusion in local forest management is becoming more a policy norm. However, these norms of women's inclusion, though still limited in space, have also come about through a process of struggle by women.